Bond-slip model for horizontal reinforcing bars in reinforced brick masonry. (15th December 2019) - Wang, Zuowei; Zhao, Jianchang; Liu, Tingbin
Highlight: Bond performance between reinforcing bars and masonry were investigated by pull-out tests. Using a self-developed test apparatus ensured the specimen under constant pressure in the whole process. A bond-slip model that considered the effect of vertical compressive stress and bond length was proposed. Effects of various factors on the bond performance were evaluated. Good agreement between model predictions and test results was achieved. Abstract: The bond-slip performance and constitutive model of the interface between reinforcing steel bars and brick masonry are the basis for seismic performance analysis of reinforced masonry through finite element simulation. In this study, the gradual increase of the vertical load in masonry during construction is simulated using a convenient self-developed test setup that ensures that the specimen is under constant pressure based on the actual stress state of horizontal reinforcing steel bars in reinforced brick masonry. Both the vertical compressive stress and the bond length were considered as variables and were used to form 19 groups of specimens. The bond characteristics of reinforcing steel bars were investigated using pull-out tests. The bond-slip curves of the interface between the horizontal reinforcing steel bar and brick masonry were obtained from test data; then, a five-segment bond-slip model that considered the effect of the vertical compressive stress and the bond length on the bond performance is proposed. This study analysed the variation trend of the bond parameters of each feature point influencing the bond performance in the model. The initial bond stiffness of the micro-slip segment increased with the increase in the vertical compressive stress, and the ultimate bond stress increased significantly. The calculation formulas of the bonding parameters are obtained by regression statistics taking these factors into consideration. The predictions obtained from the model show good agreement with test results.